Encyclopedia of algorithms - Kao, Ming-Yang (Springer reference, 2008)
One of Springer's renowned Major Reference Works, this defining reference provides a comprehensive set of solutions to important algorithmic problems for students and researchers. No comparable reference work on this subject is available, making this a genuine must-have for computer scientists.